TV white spaces with geo-location database access: practical considerations and trials in Europe - Dionísio, Rogério (2017)
This chapter describes outdoor transmission tests and field measurements in TV white spaces (TVWS) carried out in Europe. TVWS Measurements in Germany showed that the extended Hata model is appropriate to describe the path loss over distances up to a few kilometers. During the TVWS trial in Slovenia, we combine infrastructure sensing with geo-location database access to protect not only DVB-T, but also wireless microphone (WM) signals from TVWS devices interference.